Construction of College English Expansion Curriculum System for Ethnic Minorities Under the Background of Big Data - Wenting Yang, Wenshu Wu (Forest Chemicals Review, 2022)
Under the circumstances that students' goal needs, learning needs and teachers' professional expertise are different, our teaching objectives, curriculum and teaching mode should also be different. It is unrealistic to expect or require all non-English major postgraduates to have high English academic communication skills. The diversified and individualized curriculum and teaching mode in line with the actual situation of colleges and universities in ethnic minority areas is the way to truly realize the concept of "adjusting measures to local conditions", "teaching students according to their aptitude" and "student-centered" foreign language education. Therefore, based on the needs analysis theory and students' English needs analysis data, this paper establishes a modular curriculum system. The system implements the rolling course selection system, small class teaching and student-centered teaching, while implementing diversified assessment methods to optimize the curriculum system. The system implements the teaching reform of English grading, classification and diversification, in order to provide inspiration and thinking for the reform of English Teaching for Postgraduates in Colleges and universities in ethnic minority areas and the development of English subjects..